1993
DOI: 10.1002/1097-0142(19931115)72:10<3007::aid-cncr2820721024>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

National survey of ovarian carcinoma VI: Critical assessment of Current International Federation of Gynecology and Obstetrics Staging System

Abstract: Background. The Commission on Cancer of the American College of Surgeons recently completed a national survey of patients with ovarian cancer. From the large database, the prognostic value of current International Federation of Gynecology and Obstetrics (FIGO) staging system for ovarian carcinoma was re‐examined. Methods. Data was collected from 25 consecutive ovarian carcinomas diagnosed in 1983 and 1988 at 904 hospitals with cancer programs. Among a total of 12,316 cases, 5156 patients had long‐term survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…An estimated 25 580 new cases of ovarian cancer were diagnosed in the United States in the year 2004, with 16 090 deaths associated with this disease (Jemal et al, 2004). Despite advances in surgical and systemic treatment, the 5-year survival of advanced stage patients with ovarian cancer remains below 30% (Nguyen et al, 1993;Parker et al, 1996;Jemal et al, 2004;Ries et al, 2004). However, invasive epithelial ovarian cancer is largely a disease of postmenopausal women with reproductive-age women comprising only 20% of all patients (Smedley and Sikora, 1985;Swenerton et al, 1985;Plaxe et al, 1993;Rodriguez et al, 1994).…”
mentioning
confidence: 99%
“…An estimated 25 580 new cases of ovarian cancer were diagnosed in the United States in the year 2004, with 16 090 deaths associated with this disease (Jemal et al, 2004). Despite advances in surgical and systemic treatment, the 5-year survival of advanced stage patients with ovarian cancer remains below 30% (Nguyen et al, 1993;Parker et al, 1996;Jemal et al, 2004;Ries et al, 2004). However, invasive epithelial ovarian cancer is largely a disease of postmenopausal women with reproductive-age women comprising only 20% of all patients (Smedley and Sikora, 1985;Swenerton et al, 1985;Plaxe et al, 1993;Rodriguez et al, 1994).…”
mentioning
confidence: 99%
“…These studies have shown that patients with early-stage disease have overall survival ranging from 60 to 100% (Nguyen et al, 1993;Kosary, 1994;Averette et al, 1995;Partridge et al, 1996;Creasman et al, 2003;Jemal et al, 2006). Previous reports on ovarian cancer survival estimates were based on patients diagnosed many years ago with outdated estimates (Young et al, 1990;Yancik, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, an estimated 22 430 new epithelial ovarian cancers were diagnosed in the United States and approximately one-third had FIGO (International Federation of Obstetrics and Gynecology) stage I and II disease with a survival rate ranging from 70 to 90% (Heintz et al, 2006;Jemal et al, 2006). Although the survival of early-stage disease is significantly higher than those with advanced cancers, approximately 20 -30% of patients with early-stage cancers will succumb to their disease (Nguyen et al, 1993;Hoskins et al, 1994;Kosary, 1994;Averette et al, 1995;McGuire et al, 1996;Heintz et al, 2006).…”
mentioning
confidence: 99%
“…This assertion has been supported by several recent publications (Jackson et al, 1997), particularly relating to ovarian cancer (Junoer et al, 1994;Kehoe et al, 1994). Ovarian cancer, the commonest gynaecological cancer, has a poor outcome, with a five-year survival of 30-40% (Nguyen et al, 1993). This has been attributed, in part, to late presentation of disease, with the majority of cases having extra-ovarian spread at diagnosis (Nguyen et al, 1996).…”
Section: Introductionmentioning
confidence: 85%